EVALUASI PENEMUAN PENDERITA BARU TB BTA POSITIF PROGRAM PENANGGULANGAN TUBERKULOSIS (P2TB) PUSKESMAS DI KABUPATEN BANTUL PROVINSI DAERAH ISTIMEWA YOGYAKARTA - , Bambang Agus Subekti; , dr. Mubasysyir Hasanbasri, MA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Tuberculosis Control Program was held in Bantul district since 1996 by using the DOTS strategy. Nationally to assess the progress and success of this program used two indicators of the case detection of new patients with positive acid resistant bacteria that is at least 70% of the estimated suspect under investigation and treatment success rate of at least 85%. Of the two indicators, in Bantul district which has not always reach the minimum target is the case detection of new tuberculosis patients with positive acid resistant bacteria which in the last 4 years (in 2006 to 2009) only reached 30% to 38%. It shows an indication of a gap in the implementation of policies and implementation programs in the field. Why this happens? Once sought out the most suitable and able to be implemented in the future. Research Objectives: Case study research to evaluate the teamwork strategy of tuberculosis control programs of public health centers in the case detection of new tuberculosis patients positive acid resistant bacteria in Bantul district of Yogyakarta. Research Methods: This study uses a case study with qualitative methods. Respondents are the chief problem areas of health, disease control section chief and deputy supervisor in the department of health, teamwork leader and the members of work teams tuberculosis control program of public health centers. Data were collected with in-depth interviews, observation and document review activities. Results: Team work using job descriptions that refer to the duties and functions of each member in his profession. So that team members work only using job descriptions are general and work in teams as a secondary activity. The training material is only oriented program management, clinical and technical course, the evaluation system of training and update knowledge has not been appropriate, so it is not able to build a dynamic team performance and functional. Supervision is carried out either by the health department supervisor and head of community health centers are just a formality, administrative and coordinative. Support the leadership is not in accordance with the expectations of the teamwork and its members.